Enhancement in Antagonistic Biopotentiality of Trichoderma viride (Pers.) through UV Mutagenesis against Sclerotium rolfsii - C.R. KSHIRSAGAR*, K.K. SAINI and (Indian Phytopathology, 2016)
Four efficient mutant strains were obtained from the wild T. viride strain after UV treatment of different time period exposure ranging from 20 to 80 minutes. Selected mutants were tested for in vitro inhibition of Predominant soilborne fungal pathogen Sclerotium rolfsii by using various plate culture techniques (dual culture, inverted plate technique) for their bio-efficacy. In dual culture studies inoculation with T. viride mutant TvM2-UV2/60 showed 89.87 per cent mycelial inhibition of Sclerotium rolfsii, which was maximum over other mutants and wild strain under study. Studies on volatile compounds that released by T. viride mutant TvM2-UV2/60 inhibited mycelia growth rate of Sclerotium rolfsii 82.72 per cent over other mutants and wild strain under study in vitro. Mutants showed better sporulation and highest growth on PDA plates and covered whole plate in 4 days than their wild type strain in 7 days. In pot culture experiment, T. viride mutants enhanced root growth than untreated control and thus helped to enhance growth of tomato seedlings.